Impact of UV irradiation in leaves, fruits and suspension-cultured cells of Micro-Tom, tomato - T. Hiramatsu; L.A. Terry; T. Kadono; Tomonori Kawano (Advances in Horticultural Science)
The present study aims to understand both positive and negative impacts of ultraviolet (UV) rays in living dwarf tomato plants (Solanum lycopersicum L. cv. Micro-Tom). This paper examines the impact of UV-C (254 nm) and UV-A (365 nm) on induction of cell death and expression patterns of pathogenesis-related (PR), stress-related and redox-related genes, namely, of 1- amincocyclopropane-1-carboxylic acid synthase (ACS1a), cytosolic ascorbate peroxidise (APX), phenylalanine ammonia-lyase (PAL), and pathogenesis-related genes (PR1 and PR-P2), in leaves, fruits (both green and red), and suspension-cultured cells of Micro-Tom. Effects of short exposure to UV-C, but not to UV-A, on induction of cell death (in cell suspension) and development of lesions accompanied by ion leakage (in the leaves) were observed while no morphological change was observed in the UV-treated green and red fruits. UV-dependent induction of PR genes (PR1 and PR-P2) in these samples suggested that UVs can be used for plant defense activation. In addition, expression of ACS1a was shown to be negatively and positively regulated by UV-C and UV-A, respectively. Thus UV-dependent postharvest controls of fruit maturity and shelf-life are likely applicable (i.e. retardation and/or acceleration of maturation).